Evaluation of primary health care in Brazil: main characteristics, limitations and potential between PMAQ and PCATool (Research, Society and Development, 2022)
Introduction: Primary Care in Health (PHC) had the Program to Improve Access and Quality of Primary Care (PMAQ-AB) as the main instrument to assess its quality until the end of 2019. It was replaced by the Primary Care Assessment Tool (PCATool) from 2020. This change was justified due to several weaknesses in the assessment instruments and their application. Objective: To identify the main characteristics of the PMAQ and PCATool assessment instruments, as well as their potential and limitations in Brazil. Material and method: This is a literature review, with a qualitative approach, based on the analysis and interpretation of official PHC assessment instruments (PMAQ and PCATool), made available by the Ministry of Health - Brazil, and scientific productions on the thematic. Results and discussion: The main differences between the instruments were perceived as the quantitative, the format/type, the organization of the items/questions, as well as the treatment and analysis of the respective data. As for the main similarities, the foundations are related to the work process of the teams and the organization of services. Both are applied to PHC users and professionals, although the PCATool does not include the Family Health Support Nucleus. Conclusion: The PMAQ instrument was considered more extensive and complex than the PCATool in terms of its variables and application. Theoretical references that supported the PMAQ instrument were not found. The external validation of the samples and psychometric properties, in addition to the high international comparability denote greater robustness and effectiveness of the PCATool.